Controlling second-harmonic generation at the nanoscale with monolithic AlGaAs-on-AlOx antennas. (16th February 2017) - Carletti, L; Rocco, D; Locatelli, A; De Angelis, C; Gili, V F; Ravaro, M; Favero, I; Leo, G; Finazzi, M; Ghirardini, L; Celebrano, M; Marino, G; et al.
Abstract: We review recent achievements in the field of nanoscale nonlinear AlGaAs photonics based on all-dielectric optical antennas. After discussing the motivation and main technological challenges for the development of an AlGaAs monolithic platform for χ (2) nonlinear nanophotonics, we present numerical and experimental investigations of the second-order nonlinear response and physical reasons for high efficiency of second-order nonlinear interactions in the AlGaAs nano-antennas. In particular, we emphasize the role of the dipolar resonances at the fundamental frequency and the multipolar resonances at the second harmonic wavelength. We also discuss second-harmonic generation directionality and show possible strategies to engineer the radiation pattern of nonlinear antennas.